Thresholds for clinical practice that directly link handgrip strength to remaining years of life: estimates based on longitudinal observational data - Sergei Scherbov; Sonja Spitzer; Nadia Steiber (BMJ Open)
Objective Muscle strength is a powerful predictor of mortality that can quickly and inexpensively be assessed by measuring handgrip strength (HGS). What is missing for clinical practice, however, are empirically meaningful cut-off points that apply to the general population and that consider the correlation of HGS with gender and body height as well as the decline in HGS during processes of normal ageing. This study provides standardised thresholds that directly link HGS to remaining life expectancy (RLE), thus enabling practitioners to detect patients with an increased mortality risk early on.Design Relying on representative observational data from the Health and Retirement Study, the HGS of survey participants was z-standardised by gender, age and body height. We defined six HGS groups based on cut-off points in SD; we use these as predictors in survival analyses with a 9-year follow-up and provide RLE by gender based on a Gompertz model for each HGS group.Participants 8156 US American women and men aged 50–80 years.Main outcome measures Z-standardised HGS and all-cause mortality.Results Even slight negative deviations in HGS from the reference group with [0.0 SD, 0.5 SD) have substantial effects on survival. RLE among individuals aged 60 years with standardised HGS of [−0.5 SD, 0.0 SD) is 3.0/1.4 years lower for men/women than for the reference group, increasing to a difference of 4.1/2.6 years in the group with HGS of [−1.0 SD, −0.5 SD). By contrast, we find no benefit of strong HGS related to survival.Conclusions HGS varies substantially with gender, age and body height. This confirms the importance of considering these heterogeneities when defining reference groups and risk thresholds. Moreover, survival appears to decrease at much higher levels of muscle strength than is assumed in previous literature, suggesting that medical practitioners should start to become concerned when HGS is slightly below that of the reference group.